Manipulating duckweed through genome duplication. (10th July 2014) - Vunsh, R.; Heinig, U.; Malitsky, S.; Aharoni, A.; Avidov, A.; Lerner, A.; Edelman, M.
Abstract: Significant inter‐ and intraspecific genetic variation exists in duckweed, thus the potential for genome plasticity and manipulation is high. Polyploidy is recognised as a major mechanism of adaptation and speciation in plants. We produced several genome‐duplicated lines of Landoltia punctata (Spirodela oligorrhiza) from both whole plants and regenerating explants using a colchicine‐based cocktail. These lines stably maintained an enlarged frond and root morphology. DNA ploidy levels determined by florescence‐activated cell sorting indicated genome duplication. Line A4 was analysed after 75 biomass doublings. Frond area, fresh and dry weights, rhizoid number and length were significantly increased versus wild type, while the growth rate was unchanged. This resulted in accumulation of biomass 17–20% faster in the A4 plants. We sought to determine if specific differences in gene products are found in the genome duplicated lines. Non‐targeted ultra performance LC‐quadrupole time of flight mass spectrometry was employed to compare some of the lines and the wild type to seek identification of up‐regulated metabolites. We putatively identified differential metabolites in Line A65 as caffeoyl hexoses. The combination of directed genome duplication and metabolic profiling might offer a path for producing stable gene expression, leading to altered production of secondary metabolites.